ОТНОШЕНИЕ ЧЕЛОВЕКА К ОКРУЖАЮЩЕЙ СРЕДЕ В ВОЗЗРЕНИЯХ ПРАВОСЛАВИЯ - Полуянов, В. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Рассматриваются проблемы отношения человека к окружающей природной среде, религиозно-нравственные основы мира и главные причины экологического кризиса. Анализируются причины обострения противоречий в системе «общество–природа», а также высказывание Русской православной Церкви о полном преодолении экономического кризиса в условиях кризиса духовного. В.П. Полуянов ВІДНОШЕННЯ ЛЮДИНИ ДО НАВКОЛИШНЬОГО СЕРЕДОВИЩА У ПОГЛЯДАХ ПРАВОСЛАВ’Я Розглядаються проблеми відношення людини до природного довкілля, релігійно–етичні основи світу і головні причини екологічної кризи. Аналізуються причини загострення протиріч в системі «суспільство–природа», а також вислів Російській православній Церкві про повне подолання економічної кризи в умовах кризи духовного. Ключові слова: екологія, православ’я, довкілля, духовність, криза, людина. V. Poluyanov THE RELATION OF THE PERSON TO ENVIRONMENT IN ORTHODOXY VIEWS Problems of the relation of the person to a surrounding environment, religious–moral bases of the world and the main reasons of ecological crisis are considered. The reasons of an aggravation of contradictions in system "society–nature", and also the statement of Russian orthodox Church about full overcoming of an economic crisis in the conditions of crisis spiritual are analyzed. Keywords: ecology, Orthodoxy, environment, spirituality, crisis, the person.